Studi Evaluasi dan Penilaian Pengelolaan Limbah B3 di PT. XY - Salma Saamiyah Desnita; Mila Dirgawati; Nico Halomoan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT XY is an industry engaged in the trading of metal goods and specialised metalworking services and the manufacture of machine parts. PT XY generates B3 waste from production and non-production processes with nine types of B3 waste, namely lead scrap, metal sludge, sewage sludge, used rags, used batteries, used refrigerants, hazardous waste packaging, used lubricating oil and electronic waste. The purpose of this research is to identify the sources, types and characteristics of hazardous waste, to evaluate the suitability of hazardous waste management from technical and non-technical aspects, and to provide recommendations in accordance with the regulations related to hazardous waste management. The research method used is the checklist method and the scoring method using the Guttman scale. The results showed that PT XY achieved a compliance result of 60.82%, the